Overview and Assessment of Unity Toolkits for Rapid Development of an Educational VR Application - Ritter, Kenneth A.; Borst, Christoph W.; Chambers, Terrence L. (International Journal for Innovation Education and Research, 2015)
As the interest in Virtual Reality (VR) increases, so does the number of software toolkits available for various VR applications. Given that more games are being made with the Unity game engine than any other game technology, several of these toolkits are developed to be directly imported into Unity. A feature and interaction comparison of the toolkits is needed by Unity developers to properly suit one for a specific application. This paper presents an overview and comparison of several virtual reality toolkits available for developers using the Unity game engine. getReal3D, MiddleVR, and Reality-based User Interface System (RUIS) are analysed for VR interaction and display on multi-projection immersive environments like Cave Automatic Virtual Environments (CAVE)s. MiddleVR was found to have the highest performance and most versatile toolkit for CAVE display and interaction. However, taking cost into account, RUIS is the clear winner as it is available for free under the Lesser General Public License (LGPL) Version 3 license.